Symposium 2: Understanding emerging knowledge spillovers in team-group learning settings: Active team learning with limited friendships - Nanclares, Nuria Hernandez; Rienties, Bart; Van den Bossche, Piet (Proceedings of the International Conference on Networked Learning, 2012)
In classroom teaching, teachers make increasingly use of collaborative learning formats such as team learning, and educational technology to enhance the learning experience of students. Most research on team-learning focuses on learning within teams. However, to what extent do learners also share knowledge between teams during a course? This study took place in a third-year course on International economics, whereby 57 students were divided into eleven teams and learned and collaborated in an innovative blended learning environment. For ascertaining whether inter- and intra-team learning and knowledge spillovers occurred during the course, we employed a method developed within the field of Social Network Analyses (SNA). We measured prior friendship relations during the first week, while possible knowledge spillovers between learners and teams were assessed during week 4, week 7 and week 14. The results indicate that knowledge spillovers across teams do occur over time. All eleven teams developed outside links to other teams after 14 weeks. Already after seven weeks, the average number of external links tripled to 20.0, which implies that the number of external links is (almost) equal to the internal links with the teams, and the E-I index was -0.12. In other words, substantial knowledge spillovers occurred after seven weeks. Finally, after 14 weeks the average number of external links was 18.4 and the External-Internal (E-I) index is -0.17, implying that in comparison to the beginning of the course learning occurred both within teams as well as outside teams but relatively more within their team rather than outside their team. Friendship relations were positively correlated to the three learning networks. However, the size of these correlations was lower than the size of correlations between the three learning networks, indicating that new learning links (i.e. knowledge spillovers) were established over time, as confirmed by follow-up multiple regression quadratic assignment procedures. Our results indicate that pre-existing friendships play a part in knowledge spillovers, but dynamics between learners and teams over time seem more important.